Application of space-time coding technique in maritime communication. (1st January 2014) - Keshav, Tushar
Development in maritime communication has swiftly increased over the past decade, however there is much more research needed to provide a perfect link. The geographically constrained nature of marine environment precludes reliable, high speed broadband wireless access at sea. To overcome this limitation, we introduce a novel approach on the application of space-time coding technique in WiMAX-based maritime communication. Since WiMAX has been lucrative in terrestrial communication system, we propose to extend the service coverage of WiMAX in marine environment. WiMAX offers a rich set of features with a number of multiple antenna techniques with their ability to exploit multipath signal propagation and achieve diversity. In this paper, we analyse the application of space-time coding technique in maritime ship-to-shore communication. In particular, we demonstrate the application of Alamouti scheme – space time block code to improve the BER of the system in various sea conditions.